Aripiprazole once-monthly for treatment of schizophrenia: double-blind, randomised, non-inferiority study. (2nd January 2018) - Fleischhacker, W. Wolfgang; Sanchez, Raymond; Perry, Pamela P.; Jin, Na; Peters-Strickland, Timothy; Johnson, Brian R.; Baker, Ross A.; Eramo, Anna; McQuade, Robert D.; Carson, William H.; Walling, David; Kane, John M.
Abstract : Background: Long-acting injectable formulations of antipsychotics are treatment alternatives to oral agents. Aims: To assess the efficacy of aripiprazole once-monthly compared with oral aripiprazole for maintenance treatment of schizophrenia. Method: A 38-week, double-blind, active-controlled, non-inferiority study; randomisation (2:2:1) to aripiprazole once-monthly 400 mg, oral aripiprazole (10–30 mg/day) or aripiprazole once-monthly 50mg (a dose below the therapeutic threshold for assay sensitivity). (Trial registration: clinicaltrials.gov, NCT00706654.) Results: A total of 1118 patients were screened, and 662 responders to oral aripiprazole were randomised. Kaplan–Meier estimated impending relapse rates at week 26 were 7.12% for aripiprazole once-monthly 400mg and 7.76% for oral aripiprazole. This difference (−0.64%, 95% CI −5.26 to 3.99) excluded the predefined non-inferiority margin of 11.5%. Treatments were superior to aripiprazole once-monthly 50mg (21.80%, P ⩽0.001). Conclusions: Aripiprazole once-monthly 400mg was non-inferior to oral aripiprazole, and the reduction in Kaplan–Meier estimated impending relapse rate at week 26 was statistically significant v. aripiprazole once-monthly 50 mg.